Ascent to the Beautiful Plato the Teacher and the Pre-Republic Dialogues from Protagoras to Symposium. - Altman, William H. F. (Lexington Books, 2020)
This book is a study of Plato's most elementary dialogues, arranged in relation to Reading Order as opposed to order of composition. Beginning with the theatrical Protagoras and reaching a mountaintop in Symposium, the dialogues between them-Alcibiades, Lovers, Hippias, Ion, and Menexenus-introduce the student to both philosophy and Platonism.